A new approach to postvasectomy semen analyses eliminates the need to evaluate a fresh specimen. (23rd November 2022) - Kiessling, Ryan J.; Hauser, Alexander; Eyre, Robert C.; Kiessling, Ann A.
Abstract: Background: According to current guidelines, confirmation that vasectomy results in sterility depends on microscopic examination of postvasectomy semen for the presence of spermatozoa. Guidelines established in 2012 require examination of a fresh specimen within 2 h of collection, which necessitates the patient making an appointment with either the surgeon's office or a licensed clinical laboratory. Twenty‐five to 42% of patients fail to comply with postvasectomy semen analysis (PVSA). Objectives: To determine if an at‐home semen collection kit can substitute for the evaluation of a fresh specimen and improve patient compliance with postvasectomy spermatozoa assessment. Materials and methods: The kit contains a patented aldehyde‐fixative that maintains spermatozoa and semen cells in suspension for quantitation. Patients order a PVSA kit to be delivered to their home and can collect a semen specimen and return it to the laboratory through regular US mail. Results: From January 2011 through December 2018, 6096 men undergoing vasectomy by 184 urologists in 33 states in the US ordered PVSA kits, of which 5408 (89%) returned at least one for analysis. Of those, 398 men (7.4%) returned the first kit with greater than 10, 000 spermatozoa/ml within a year of vasectomy, of which only 4.4% contained greater than 100, 000 spermatozoa/ml 12 weeks postsurgery. This suggests that fewer than 5% of postvasectomy patients might need follow‐up fresh semen analyses, greatly easing the logistical burden of PVSA. Ninety percent of surgeons returning a patient satisfaction questionnaire said their patients "never" complained about using PVSA kits. Discussion and conclusion: These data support the adoption of a new standard for PVSA that does not involve an initial evaluation of a fresh semen specimen.